(untitled) (Journal of Management and Social Sciences, 2018)
Abstract In the recent time, the introduction of technology into the management of electoral process has become a popular practice among democratic countries, especially in Africa. This cannot be disconnected from the argument that technology helps not only in delivering free, fair and credible elections but also that it serves as a means to increase voter turnout. Nigeria’s election management body, the Independent National Electoral Commission, introduced Smart Card Readers (SCRs) and Permanent Voter Card (PVC) during the 2015 elections with the aim of enhancing both the integrity and legitimacy of the elections. Despite this, official report from INEC showed that only 38% of registered voters cast their votes in the 2015 Kwara state gubernatorial election, a figure that represents the lowest in the history of governorship election in the state since democratic rebirth in 1999. This paper investigates the impact of technology on voter behaviour during the 2015 gubernatorial election. Adopting descriptive research design and mixed method of data collection, the paper finds that there is significant relationship between introduction of technology and voter turnout during the election. Keywords Election, technological innovation, voter turnout